2017
DOI: 10.1063/1.4978788
|View full text |Cite
|
Sign up to set email alerts
|

Study of the beam profile and position instability of a post-accelerated pseudospark-sourced electron beam

Abstract: This version is available at https://strathprints.strath.ac.uk/60089/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The theoretical analysis and the previous simulations employed uniform electron beam density distribution profiles over the beam radius. However, the electron beam density measurement using a scintillator screen showed that the PS-sourced beam has a Gaussian-like density distribution and a beam waist of 0.5 mm [27]. The injected electron beam used was of the same overall current but different density distributions.…”
Section: B the Results At Different Ion Densities Beam Energies And C...mentioning
confidence: 99%
“…The theoretical analysis and the previous simulations employed uniform electron beam density distribution profiles over the beam radius. However, the electron beam density measurement using a scintillator screen showed that the PS-sourced beam has a Gaussian-like density distribution and a beam waist of 0.5 mm [27]. The injected electron beam used was of the same overall current but different density distributions.…”
Section: B the Results At Different Ion Densities Beam Energies And C...mentioning
confidence: 99%
“…The PS discharge goes through various complex discharge processes and depends primarily on the PS discharge configurations [24][25][26][27][28][29]. Since its discovery in 1978, efforts have been made to understand the PS discharge phenomena for the generation of high density and energetic electron beams by theoretical, plasma simulation, and experimental studies [9,18,24,[29][30][31][32][33][34][35][36][37][38]. Notably, PS discharges have been studied at the University of Strathclyde since 1994 with a series of experiments conducted on beam generation and microwave and millimetre wave sources driven by PS discharges.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve better beam quality, the PS-sourced electron beam is also investigated with post-acceleration to reduce its beam energy spread [8][9][10]. To achieve higher output power, a sheet beam EIO structure is further studied with a PS-sourced sheet beam [11].…”
Section: Introductionmentioning
confidence: 99%